2008
DOI: 10.1016/j.jneumeth.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Increased lactate levels and reduced pH in postmortem brains of schizophrenics: Medication confounds

Abstract: A number of postmortem studies have found decreased pH in brains of patients with schizophrenia. Insofar as lower pH has been associated with decreased mRNA expression in postmortem human brain, decreased pH in schizophrenia may represent an important potential confound in comparisons between patients and controls. We hypothesized that decreased pH may be related to increased concentration of lactic acid. However, in contrast to the previous notion that an increase in lactic acid represents evidence for primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
96
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 32 publications
8
96
1
Order By: Relevance
“…While two earlier NMR studies of frontal cortex and thalamus reported no statistically significant differences in these metabolites in schizophrenia (Omori et al 1999, Prabakaran et al 2004), small reductions in both lactate and alanine levels were noted in the thalamus (Omori et al 1999). However, our finding of lower lactate in ventral ALIC differs from two previous post-mortem studies that found higher lactate levels in frontal white matter (Prabakaran et al 2004) and cerebellum (Halim et al 2008) in schizophrenia. Glycogen is rapidly converted into lactate post-mortem.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While two earlier NMR studies of frontal cortex and thalamus reported no statistically significant differences in these metabolites in schizophrenia (Omori et al 1999, Prabakaran et al 2004), small reductions in both lactate and alanine levels were noted in the thalamus (Omori et al 1999). However, our finding of lower lactate in ventral ALIC differs from two previous post-mortem studies that found higher lactate levels in frontal white matter (Prabakaran et al 2004) and cerebellum (Halim et al 2008) in schizophrenia. Glycogen is rapidly converted into lactate post-mortem.…”
Section: Discussioncontrasting
confidence: 99%
“…No other protein measures showed significant correlations with age, PMI, pH or duration of storage. Lactate levels were inversely correlated with pH (rho=−0.576, p=0.001) as expected from previous studies (Halim et al 2008). Lactate is a major determinant of brain pH; therefore we did not use pH as a covariate in the metabolite analysis.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In humans, the use of higherrange therapeutic doses of Met is unlikely to be of consequence unless elimination of Met is compromised (i.e., renal failure). That said, serious mental illnesses such as schizophrenia and bipolar disorder have been associated with mitochondrial dysfunction and increased lactate levels (Halim et al 2008, Regenold et al 2009, Herberth et al 2011, which raises the unexplored possibility that our patients may require more judicious dosing of Met to obtain maximal benefits. Translation of findings from rodents to clinic may, however, be complicated by genetic factors mediating metabolism and therapeutic action of Met (Shu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One is that under pathological conditions such as hypoxia and schizophrenia, the extracellular pH in the brain can change (Chesler and Kaila, 1992; Halim et al, 2008; Siesjo, 1985) which in turn can change the effect of NMDAR modulators (Kostakis et al, 2011; Mott et al, 1998). Secondly, as exemplified by the potentiating actions of spermine on NMDARs (Traynelis et al, 1995), reversing proton inhibition is a potential mechanism of action for an NMDAR PAM.…”
Section: Resultsmentioning
confidence: 99%